Exploring the Evolution of Storytelling in the Streaming Era: A Study of Narrative Trends in Netflix Original Content - Katerynych, Petro; Goian, Vita; Goian, Oles (Communication Today, 2024)
In this longitudinal study, we examine the changing landscape of storytelling in the streaming era, with a specific focus on Netflix’s original content from 2016 to 2022. Our primary goal is to understand the evolving patterns of storytelling techniques employed by Netflix during this period. We reviewed 150 original Netflix productions, consisting of 100 series and 50 movies, representing approximately one-third of Netflix’s original releases during the specified time period. Our analysis includes ten different storytelling criteria, including nonlinear, serialised, character-driven, documentary, anthology, flashback, episodic, interconnected, immersive, and real-time storytelling techniques, across both English and non-English content. The analysis revealed dynamic trends in the use of these storytelling techniques. Nonlinear storytelling, flashback storytelling, documentary-style and interconnected storytelling have shown positive correlations over time, indicating their increasing popularity. In contrast, serialised, anthology, and real-time storytelling have negative correlations, suggesting fluctuations or declining use. The analysis supports the alternative hypothesis (H1) that there is a significant shift, with an increasing emphasis on nonlinear storytelling, flashback storytelling, and interconnected storytelling. These findings underscore the ever-changing nature of Netflix’s storytelling methods, shedding light on the importance of adapting to audience preferences and evolving trends in the streaming industry.